No effects of caffeine on cycling to exhaustion and perceptual responses in non-caffeine-restricted subjects - Weippert, Matthias; Behrens, Martin; Schlegel, Martin; Schröder, Tom; Tillmann, Moritz; Rühe, Nelly; Römer, Robert; Mau-Möller, Anett; Bruhn, Sven (Journal of the International Society of Sports Nutrition, 2025)
Caffeine has been shown to improve endurance performance probably primary due to its pharmacological effects in the central nervous system modifying, among others, the perceptual responses during exercise. However, most studies proving the performance-enhancing effects of caffeine utilized an experimental caffeine restriction phase prior to the measurement sessions. Therefore, the effects of 2.5 and 6 mg*kg oral caffeine ingestion on endurance performance, perceptual, affective, and cognitive responses during exercise, as well as time perception, were investigated in participants following their normal "ad libitum" daily diet. Two double-blinded, randomized placebo-controlled cross-over studies were performed to test the effect of 2.5 ( = 35, age: 23.3 ± 3.5 years, habitual caffeine consumption of 106 ± 89 mg*day ) and 6.0 mg*kg ( = 21, age: 21.2 ± 2.3 years, habitual caffeine consumption of 87 ± 64 mg*day ) oral caffeine ingestion on time to exhaustion (TTE), perceived fatigue, perceptual-discriminatory (effort perception, physical strain), affective-motivational (affective valence, arousal, dominance, motivation, boredom), and cognitive-evaluative responses (decisional conflict, attentional focus) as well as time perception (time production and estimation) and heart rate during cycling at 65% peak power. Participants were low-to-moderate caffeine consumers (one participant in each study reported no habitual caffeine intake) and asked to follow their regular "ad libitum" diet without any restrictions regarding caffeinated beverages and/or food during the studies. Neither a dose of 2.5 nor of 6.0 mg*kg was found to be superior to placebo with respect to TTE, perceived fatigue, the perceptual-discriminatory, affective-motivational, and cognitive-evaluative responses to exercise, as well as time perception. Both dosages of caffeine had no effect on TTE, perceived fatigue, perceptual-discriminatory, affective-motivational, and cognitive-evaluative responses to exercise, as well as on time perception and heart rate in low-to-moderate caffeine consumers without a prior experimental caffeine restriction phase. The findings suggest that caffeine´s positive effects on endurance performance and perceptual responses to exercise found in previous studies might be partly explained by the reversal of adverse effects induced by a prior caffeine restriction phase.